Advances in the clinical application of orthotic devices for stroke and spinal cord injury since 2013 - Cui, Yinxing; Cheng, Shihuan; Chen, Xiaowei; Xu, Guoxing; Ma, Ningyi; Li, He; Zhang, Hong; Li, Zhenlan (Frontiers in Neurology, 2023)
Stroke and spinal cord injury are common neurological disorders that can cause various dysfunctions. Motor dysfunction is a common dysfunction that easily leads to complications such as joint stiffness and muscle contracture and markedly impairs the daily living activities and long-term prognosis of patients. Orthotic devices can prevent or compensate for motor dysfunctions. Using orthotic devices early can help prevent and correct deformities and treat muscle and joint problems. An orthotic device is also an effective rehabilitation tool for improving motor function and compensatory abilities. In this study, we reviewed the epidemiological characteristics of stroke and spinal cord injury, provided the therapeutic effect and recent advances in the application of conventional and new types of orthotic devices used in stroke and spinal cord injury in different joints of the upper and lower limbs, identified the shortcomings with these orthotics, and suggested directions for future research.